Brain-wide slowing of spontaneous alpha rhythms in mild cognitive impairment - Garcés, Pilar; Vicente, Raul; Wibral, Michael; Pineda Pardo, Jose Angel; Lopez, Maria Eugenia; Aurtenetxe, Sara; Marcos, Alberto; de Andrés, Maria Emiliana; Yus, Miguel; Sancho, Miguel; Maestú, Fernando; Fernández, Alberto (Frontiers in Aging Neuroscience, 2013)
The neurophysiological changes associated with Alzheimer’s Disease (AD) and Mild Cognitive Impairment (MCI) include an increase in low frequency activity, as measured with electroencephalography or magnetoencephalography (MEG). A relevant property of spectral measures is the alpha peak, which corresponds to the dominant alpha rhythm. Here we studied the spatial distribution of MEG resting state alpha peak frequency and amplitude values in a sample of 27 MCI patients and 24 age-matched healthy controls. Power spectra were reconstructed in source space with linearly constrained minimum variance beamformer. Then, 88 Regions of Interest (ROIs) were defined and an alpha peak per ROI and subject was identified. Statistical analyses were performed at every ROI, accounting for age, sex and educational level. Peak frequency was significantly decreased (p< 0.05) in MCIs in many posterior ROIs. The average peak frequency over all ROIs was 9.68±0.71 Hz for controls and 9.05±0.90 Hz for MCIs and the average normalized amplitude was (2.57±0.59)•10-2 for controls and (2.70±0.49)•10-2 for MCIs. Age and gender were also found to play a role in the alpha peak, since its frequency was higher in females than in males in posterior ROIs and correlated negatively with age in frontal ROIs. Furthermore, we examined the dependence of peak parameters with hippocampal volume, which is a commonly used marker of early structural AD-related damage. Peak frequency was positively correlated with hippocampal volume in many posterior ROIs. Overall, these findings indicate a pathological alpha slowing in MCI.